2015
DOI: 10.1037/stl0000041
|View full text |Cite
|
Sign up to set email alerts
|

Testing together: When do students learn more through collaborative tests?

Abstract: Tests are powerful learning tools when students complete them alone, but in practice, testing sometimes manifests as a group exercise. Collaborative learning approaches are generally embraced by educators although research in this area is mixed. Two questions linger: What memory mechanisms are at play when students test in groups? And when is collaborative testing most likely to enhance learning above and beyond individual testing? This article reviews both laboratory and applied research on collaborative test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 97 publications
(131 reference statements)
1
17
0
Order By: Relevance
“…By design, the group portion of the examination facilitates high levels of engagement. It has been hypothesized that the immediate feedback and group discussion are the key features that yield improved test taking skills, improved retention of knowledge, and reduced test anxiety that ultimately result in improved performance on examinations (Giuliodori et al, ; Gilley and Clarkston, ; Rieger and Heiner, ; LoGiudice et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…By design, the group portion of the examination facilitates high levels of engagement. It has been hypothesized that the immediate feedback and group discussion are the key features that yield improved test taking skills, improved retention of knowledge, and reduced test anxiety that ultimately result in improved performance on examinations (Giuliodori et al, ; Gilley and Clarkston, ; Rieger and Heiner, ; LoGiudice et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies of mostly low-stakes collaborative testing have indicated that collaborative testing can improve learning by reexposing students to material (reexposure), prompting them to retrieve the information either from memory (retrieval) or through cueing from team members (cross-cueing), and helping students reject misinformation (error pruning). 1 These mechanisms may have also been at play for our results. Additional studies are needed in this area.…”
Section: Insightsmentioning
confidence: 79%
“…[1][2][3][4] Studies of collaborative testing within the classroom setting suggest that it can improve academic performance, critical thinking, communication, and teamwork skills while decreasing test anxiety. [1][2][3][4] Studies in nursing education and exercise physiology show that collaborative testing improves retention of content. [5][6] Other publications 7 suggest that collaborative testing can result in increased retention of concepts that were originally missed by a student.…”
Section: Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation
“…Rieger and Heiner (2014) found that students were generally positive in their collaborative exam experience 76% of the time, neutral 14% of the time, and had negative experiences 10% of the time. Similarly, many studies over the past 15 years have reported positive experiences during collaborative exams, from reductions in test anxiety to perceptions of enhanced learning (for a review, please see LoGiudice et al. , 2015).…”
Section: Discussionmentioning
confidence: 99%